Influence of the window profile on the final quality of the product - Jevtoska, Elena (My University, 2023)
The current product on the market offers a wide range of diverse profiles for producing windows that are made of different materials, width and order of grills depending on the profile. Within the framework of this research the windows with same dimensions shall be elaborated, those which are made of the same production capacity and use the same fittings but different types of PVC profiles. The aim is to prove what kind of influence the used profile has over the final quality of the product. For this research, two groups and six subgroups will be tested. In each subgroup, one tests five windows made of the same profile. The groups are divided according to the used fittings. The testing of the quality shall be conducted in accordance with the European norms EN 1026:2016 (Windows and doors - Air permeability - Test method), EN 1027:2016 (Windows and doors - Water tightness - Test method), EN 12211:2016 (Windows and doors - Resistance to wind load - Test method).
Keywords: CONSTRUCTION CARPENTRY, WINDOW, AIR PERMEABILITY, WIND RESISTANCE, PVC PROFILES